Faktor Yang Berhubungan Dengan Kejadian Stunting Usia 24-59 Bulan Di Wilayah Kerja Puskesmas Maiwa - Sahrani; Andi Surahman Batara; Reza Aril Ahri; Arman; Mansur Sididi (Window of Public Health Journal, 2025)
Stunting, or short stature, is a nutritional status based on the height-for-age (W/A) index with a z-score of less than -2 SD (Standard Deviation). Stunting is not only a problem of impaired physical growth but also makes children susceptible to illness. In addition, brain development and intelligence are also impaired. Therefore, stunting is a major threat to the quality of human resources in Indonesia. This study aims to determine the factors associated with the incidence of stunting in children aged 24-59 months at the Maiwa District Health Center, Enrekang Regency. The study is an analytical observational study with a quantitative approach using a cross-sectional study. The population in this study was toddlers aged 24-59 months. The sampling technique used was purposive sampling. The data analysis method used was bivariate analysis with the chi-square test. The results of this study obtained maternal knowledge, maternal MUAC (mid-upper arm circumference) during pregnancy, LBW, birth length did not have a significant relationship with the incidence of stunting where ρ = 0.072, ρ = 0.093, ρ = 0.082, ρ = 0.119 means ρ> 0.05, and a history of infectious diseases had a significant relationship with the incidence of stunting where ρ = 0.024 means ρ <0.05. It can be concluded that there is no significant relationship between knowledge, maternal LILA during pregnancy, LBW, and birth length with the incidence of stunting, so Ha is rejected. And there is a significant relationship between the history of infectious diseases and the incidence of stunting, so Ha is accepted.